Indigenous archaeology in the Philippines decolonizing Ifugao history - Acabado, Stephen B.; Martin, Marlon (Tucson The University of Arizona Press, 2022)
"This book illustrates how descendant communities can take control of their history and heritage through active collaboration with archaeologists. Drawing on the Philippine Cordilleran experiences, Indigenous Archaeology in the Philippines discusses how changing historical narratives help empower peoples who are traditionally ignored in national histories"
Introduction: Peoples Without History -- 1. The Ifugao: People and Landscape -- 2. From the Outside Looking In: Dominant Historical Narratives -- 3. Older Is Not Necessarily Better: Dating of the Rice Terraces -- 4. Ifugao Archaeology -- 5. Rice and Craft Production -- 6. The Archaeology of Colonial Co-optation -- 7. Colonialism Without Colonization: Pericolonialism -- 8. When the Empire Strikes: Assimilationist Policies, Archaeology, and Politics -- 9. The Rise of Indigenous Empowerment: From Participatory Archaeology to Ifugao Archaeology -- 10. Making Their Own History -- Epilogue.
Includes bibliographical references and index.
Keywords: Ifugao (Philippine people) -- History; Philippines -- Antiquities